CYBERSECURITY ISSUES IN JOURNALISM BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Sunbul Zalova (Problems of Information Society)
Although the use of artificial intelligence in journalism creates innovations and opportunities, this process leads to complications in a number of cybersecurity issues. One of the main problems is the risk of disinformation and manipulation. Although artificial intelligence algorithms automatically process information, it is possible for these algorithms to make decisions based on incorrect information, which can result in the dissemination of biased or false news. At the same time, the database used in artificial intelligence programming can affect its objectivity and impartiality. The use of data collected by artificial intelligence and sources without verification can lead to the dissemination of untrustworthy and inaccurate news. This article examines cybersecurity issues arising from the application of artificial intelligence technologies in journalism. Artificial intelligence technologies are currently widely used at all stages of news production. It highlights the current situation regarding artificial intelligence technologies and the application of these technologies to journalism, as well as the problems encountered in this field. This article examines the problems arising from the application of artificial intelligence technologies. “Deepfake” technologies, their negative aspects, and the problems they may cause are studied. Proposals are made for solving cybersecurity issues and a conceptual model is developed.